Teachers' Profesionalism and Challenges in Industrial Revolution Era 4.0 - Supriyono Supriyono (Universitas Sebelas Maret, 2019)
This paper discusses the concept of teachers' profesaionalism and challenges in facing the industrial revolution era 4.0. In this case, teachers have a very important role at schools in utilizing various learning approaches. The traditional learning (teacher-centered) approach long implemented for years has now been considered out of date that student-centered learning replaces the approach. The teachers' role has recently shifted that teachers now become the facilitators for their learners. These shifting learning approach has become an inevitabity to anticipate that a concret action is greatly required. Educational world should be able to manage itself by making some renewals and innovations related to the management system, curriculum, Human Resource Competence Development, culture, working ethics, and facilities. This study uses references related to the nature of teachers' profesionalism, industrial revolution 4.0, and various challenges. Concrete actions need to be well prepared as well as creatively, dynamically, and innovatively made. Thus, it can be concluded that teachers should be able to maintain their professionalism in performing their daily duties and obligations.